Cuir-writing, infected research: the unmaking of research in art from the edges of the world. (Palíndromo, 2026)
This text was written collectively by the coordinators of the research group FIGAS (Feminisms, Images, Genders, Arts and Sexualities), tied to the Art Institute of Unesp, with the aim of contaminating the production of knowledge with the virus of deviation. Here, a conversation takes place between the researchers, the authors cited, and you, the reader. The themes contaminate each other: methods of research in the arts and art as a method of research. Questions about form, matter, aesthetics, deconstruction, cuir procedures, and feminisms emerge, cutting through the dialogue. The methodological procedure used is that developed collectively by the group: contaminated research or contamination itself. The result is an article-work-of-art contaminated by theatrical text, children's stories, and gossip. The conclusions, if any, are multiple.
Keywords: feminisms; images; genders; arts; sexualities